Accurate absolute core-electron binding energies of molecules, solids and surfaces from first-principles calculations - Kahk,JM; Lischner,J (Physical Review Materials, 2019)
Core-electron x-ray photoelectron spectroscopy is a powerful technique for studying the electronicstructure and chemical composition of molecules, solids and surfaces. However, the interpretationof measured spectra and the assignment of peaks to atoms in specific chemical environments is oftenchallenging. Here, we address this problem and introduce a parameter-free computational approachfor calculating absolute core-electron binding energies. In particular, we demonstrate that accurateabsolute binding energies can be obtained from the total energy difference of the ground state anda state with an explicit core hole when exchange and correlation effects are described by a recentlydeveloped meta-generalized gradient approximation and relativistic effects are included even forlight elements. We carry out calculations for molecules, solids and surface species and find excellentagreement with available experimental measurements. For example, we find a mean absolute errorof only 0.16 eV for a reference set of 103 molecular core-electron binding energies. The capability tocalculate accurate absolute core-electron binding energies will enable new insights into a wide rangeof chemical surface processes that are studied by x-ray photoelectron spectroscopy.